Diversity and Distribution of Gastropods in the Southern Coastal Area of Gunungkidul, Yogyakarta - Dyah Wahyu Setyaningsih; Partaya (Universitas Negeri Semarang, 2025)
The southern coast of Gunungkidul, Yogyakarta, exhibits high gastropod diversity across varied substrates, offering a critical framework to study their distribution and ecological role in coastal ecosystem balance. This study aims to analyze the level of gastropod diversity and distribution in the Sundak Beach, Indrayanti Beach, and Drini Beach areas to support area management and maintain the survival of organisms and water productivity. Research was conducted using a 1x1 meter quadrat plot method systematically placed in the intertidal zone at three coastal locations. Data collection was carried out over a period of three months (October–December 2024). Gastropod species identification was based on shell morphological characteristics, while data analysis included calculations of the Shannon-Wiener diversity index (H’), Simpson dominance index (C), Pielou evenness index (E), abundance (ind/m2), and Morisita dispersion index (Id) to determine distribution patterns. Environmental parameters measured included temperature, pH, and salinity. The results found 23 gastropod species from 12 families across the three study locations, with high diversity values (H’ = 2.63), high evenness (E = 0.84), and low dominance (C = 0.10). The distribution pattern of most species was clumped, influenced by food availability and substrate characteristics. Environmental factors such as temperature (28–31°C), pH (7), and salinity (30–32%) supported the stability of gastropod communities. The findings are expected to provide scientific insight into their community structure and an understanding of the environmental factors influencing their abundance in the intertidal zone.